2014
DOI: 10.1080/08870446.2014.885523
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal postnatal depression on men and their ways of fathering: an interpretative phenomenological analysis

Abstract: Evidence indicates that maternal postnatal depression can exert substantial effects on mothers, fathers and their children. There are conflicting findings about the extent to which fathers can buffer against the negative effects of maternal depression on children, and we understand relatively little about what shapes the way men father in the context of maternal postnatal depression. The present study explored men's accounts of fathering when their partner(s) was postnatally depressed. Narrative interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 90 publications
(70 reference statements)
1
37
0
1
Order By: Relevance
“…In terms of the experience of parenting, findings were diverse, with some participants reporting harmonious parenting, in which they felt 'in-tune' and collaborated with their partner (Marrs et al 2014;Reid et al 2017;Webster 2002), while others described feelings of being criticised and excluded by their partner (Beestin et al 2014;Boddy et al 2017;Davey et al 2006;Engqvist and Nilsson 2011). For those men who found they were parenting alone due to their partners' physical or psychological absence, feelings of solitude and burden prevailed (Beestin et al 2014;Wyatt et al 2015).…”
Section: Parenting Togethermentioning
confidence: 99%
“…In terms of the experience of parenting, findings were diverse, with some participants reporting harmonious parenting, in which they felt 'in-tune' and collaborated with their partner (Marrs et al 2014;Reid et al 2017;Webster 2002), while others described feelings of being criticised and excluded by their partner (Beestin et al 2014;Boddy et al 2017;Davey et al 2006;Engqvist and Nilsson 2011). For those men who found they were parenting alone due to their partners' physical or psychological absence, feelings of solitude and burden prevailed (Beestin et al 2014;Wyatt et al 2015).…”
Section: Parenting Togethermentioning
confidence: 99%
“…Qualitative research has shown that partners experience fear, confusion, concern, helplessness, frustration, isolation, and stigma when a woman has postnatal depression (Davey, Dziurawiec, & O'Brien-Malone, 2006;Engqvist & Nilsson, 2011;Meighan, Davis, Thomas, & Droppleman, 1999). They describe a sense that their coparent is "absent," resulting in loneliness and feelings of responsibility for "filling the void" (Beestin, Hugh-Jones, & Gough, 2014). Where women are admitted to a hospital with severe perinatal psychiatric difficulties, partners report shock and disbelief, trauma, stress, financial and work-related difficulties, relationship problems, and sleep deprivation (Muchena, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although, not typically considered a mental health condition, high levels of stress may contribute to maternal depression and anxiety [Farr et al, ] and are associated with many other poor health outcomes [Glover, ]. Postpartum mental health symptoms are associated with physical and mental health consequences for mothers and their families, including insecure infant attachment, child intellectual difficulties, and a diminished relationship with the romantic partner [Hay et al, ; Davey et al, ; Groer and Morgan, ; Beestin et al, ; Farr et al, ; Zietlow et al, ].…”
Section: Introductionmentioning
confidence: 99%